2008
DOI: 10.1128/jb.00896-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Spores of Bacillus subtilis That Lack Most Coat Layers

Abstract: Spores of Bacillus subtilis have a thick outer layer of relatively insoluble protein called the coat, which protects spores against a number of treatments and may also play roles in spore germination. However, elucidation of precise roles of the coat in spore properties has been hampered by the inability to prepare spores lacking all or most coat material. In this work, we show that spores of a strain with mutations in both the cotE and gerE genes, which encode proteins involved in coat assembly and expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
88
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 43 publications
(66 reference statements)
6
88
0
Order By: Relevance
“…We use the Mn(II)-induced 2 H spin relaxation to identify the magnetization component associated with the core, but we remove Mn(II) ions outside the core by EDTA to reveal the water dynamics in the cortex and coat. Further information was obtained by examining coat-deficient spores from a B. subtilis strain with mutations in the cotE and gerE genes (27). Unexpectedly, we found that the water permeability of the IM is greatly enhanced in these coat-deficient spores.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…We use the Mn(II)-induced 2 H spin relaxation to identify the magnetization component associated with the core, but we remove Mn(II) ions outside the core by EDTA to reveal the water dynamics in the cortex and coat. Further information was obtained by examining coat-deficient spores from a B. subtilis strain with mutations in the cotE and gerE genes (27). Unexpectedly, we found that the water permeability of the IM is greatly enhanced in these coat-deficient spores.…”
mentioning
confidence: 75%
“…Because the cortex peptidoglycan network (18) is not expected to trap water molecules for periods Ͼ10 ns (35), the low-frequency dispersion must be produced by internal water molecule in the coat layers, comprising Ϸ55% of total spore protein (37). The coat proteins, organized in dense, cross-linked layers (20,27), are expected to be rotationally immobilized and they should therefore contribute to the low-frequency dispersion (23,24).…”
Section: Internal Water In Coat Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bacillus subtilis strains used in this work were either the wild type PS533 or the coat deficient strain PS4150 in which most of the cotE and gerE coding sequences are deleted [15]. PS533 and PS4150 (both from the Department of Molecular, Microbial, and Structural Biology, University of Connecticut Health Center, USA) are the derivatives of isogenic strain PS832, a prototrophic derivative of a strain 168.…”
Section: Spores Productionmentioning
confidence: 99%
“…However, the composition of spores is not the only factor responsible for its extreme resistance, and the structure itself is thought to play a role in protection from chemicals and physical stress [12]. For example, a weak permeability of the inner membrane might prevent or slow down the entry of chemical agents deleterious to DNA [13] and the proteinaceous coat should protect spores from digestion by bacterivores as well as against some chemicals, such as iodine or oxidative agents [14][15][16].…”
Section: Introductionmentioning
confidence: 99%